Cutting from Within: the Electoral Strategy of the Indonesian Communist Party, 1955-1957 - Desvian Bandarsyah; Rizkindo Junior; Sulaeman (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: The Indonesian Communist Party is among the major parties in the period of liberal democracy. The party's development was supported by a strategy of welcoming the 1955 General Elections for the DPR and the Constituent Assembly, followed by the 1957 DPRD elections. Therefore, this research aimed to analyze the strategy of the Indonesian Communist Party (PKI) in facing the struggle of the 1955 General and 1957 Regional Elections. The research was conducted using a historical method comprising four steps: heuristics, source criticism, interpretation, and historiography. The results showed that Marxism–Leninism served as the ideological foundation of the PKI, guiding its strategic development and strengthening party doctrine through the establishment of the National Unity Front. This initiative mobilized and integrated non-party organizations in pursuit of democratic objectives during the 1955 elections, while also strengthening national coalitions to consolidate the opposition against rival parties. In the 1957 regional elections, the PKI sharply criticized other parties for corruption and accused them of being traitors to the people's revolution. This strategy succeeded in splitting and winning votes from other parties. Therefore, PKI ranked among the top four parties with 6,000,000 and 8,500,000 votes in the 1955 General and 1957 Regional Elections, respectively. PKI succeeded in positioning the party with a strategy of coalition and attacking others for corruption. This study contributes to historiography by highlighting the role of ideological consolidation and mass mobilization in electoral success, offering insights into the dynamics of political strategy in post-independence Indonesia. Abstrak: Partai Komunis Indonesia (PKI) merupakan salah satu partai besar pada masa demokrasi liberal. Perkembangan partai ini didukung oleh strategi dalam menyambut Pemilu 1955 untuk DPR dan Konstituante, yang kemudian dilanjutkan dengan pemilihan DPRD tahun 1957. Oleh karena itu, penelitian ini bertujuan untuk menganalisis strategi PKI dalam menghadapi kontestasi Pemilu 1955 dan Pemilihan Daerah 1957. Penelitian ini menggunakan metode sejarah yang meliputi empat tahapan, yaitu heuristik, kritik sumber, interpretasi, dan historiografi. Hasil penelitian menunjukkan bahwa Marxisme–Leninisme menjadi landasan ideologis PKI yang mengarahkan pengembangan strategi serta memperkuat doktrin partai melalui pembentukan Front Persatuan Nasional. Inisiatif ini berhasil memobilisasi dan mengintegrasikan organisasi-organisasi nonpartai untuk mencapai tujuan demokratis dalam Pemilu 1955, sekaligus memperkuat koalisi nasional dalam menghadapi partai-partai pesaing. Dalam pemilihan daerah tahun 1957, PKI melancarkan kritik tajam terhadap partai-partai lain yang terlibat korupsi dan dianggap mengkhianati revolusi rakyat. Strategi ini berhasil memecah basis dukungan lawan sekaligus menarik suara dari partai lain. Sebagai hasilnya, PKI berhasil menempati posisi empat besar dengan perolehan sekitar 6.000.000 suara pada Pemilu 1955 dan 8.500.000 suara pada Pemilihan Daerah 1957. PKI berhasil mengukuhkan posisinya melalui strategi koalisi serta serangan politik terhadap praktik korupsi lawan. Penelitian ini memberikan kontribusi pada historiografi dengan menyoroti peran konsolidasi ideologi dan mobilisasi massa dalam keberhasilan elektoral, serta memberikan pemahaman mengenai dinamika strategi politik pada masa awal pascakemerdekaan Indonesia.